Conhecimento de preceptores da residência multiprofissional em saúde sobre metodologias de ensino - Sousa, Núbia Maria Lima de (2017)
Preceptory in health in university hospitals has become a pedagogical practice and many service professionals were inserted as preceptors, but most of them did not have education training. Finding difficulties in adopting teaching-learning strategies that bring scientific knowledge closer to practical reality in the training of health professionals. This study aims to analyze the knowledge of teaching methodologies by preceptors (teachers) in the teaching/learning process of multiprofessional residents in health. It is a descriptive, cross-sectional study with a qualitative approach, composed with 50 preceptors who had been working for more than one year in the multiprofessional health residency of a school hospital. Data collection was carried out from September to December 2016, through a semistructured script to characterize the subjects of study and with the application of the word-free association technique. Data were analyzed by the Ensemble software of Permettant L'Analyse des Evocations (EVOC), version 2000, and discussed based on the theoretical framework of the Core Nucleus Theory. It was approved by the Research Ethics Committee under no. 1.663.421 / 16. Data were divided into three thematic units: knowledge of preceptors about teaching strategies, about traditional methodology and active methodologies and their respective categories: conceptual elements; practical theoretical use, deepening of content and applicability. The items with the lowest mean order of evocation (MOE), with a parameter by 2.0, 2.3 and 2.5 and higher frequency (F) with a parameter by 10, were considered with elements of the central nucleus. In the thematic unit referring to teaching strategy, the words stood out the words, such as "teaching method" (MOE, 1,4- F29). "Dynamic" (MOE 1.6 - F 13) and "lessons" (MOE 2.0 - F17). The traditional methodology was represented by "archaic teaching" (MOE 1.7 - F 45) and "teacher-centered" (MOE 1.8 F 22). For the active methodologies "proactivity" (MOE 1,7 - F 23), "constructivism" (MOE1, 9 F 61) and "feedback" (MOE 2.1 F10) stood out. The study pointed out that preceptors have understood the teaching strategies with methods that have favored learning teaching. Moreover, it has evidenced the knowledge about traditional methodologies, such as "archaic teaching" and "content methodology" and active methodologies, such as "proactivity", "constructivism" and "feedback", although most points out the non-use of this in the teaching of multiprofessional residency in health. Finally, it is believed that for the training of professionals in the area of health, there must be an interdisciplinary character, using active methodologies that awaken in the student his/her reflexive-critical potential, making him/her a transforming agent in the process of caring for the subjects in the different scenarios of professional activity proposed by Unified Health System. As a product of this study, a proposal was created to train the preceptors of the multiprofessional health residency, field of study, in active teaching methodologies.